Wide‐Gap Chalcopyrite Solar Cells with Indium Oxide–Based Transparent Back Contacts. Issue 8 (31st May 2022) - Keller, Jan; Stolt, Lars; Donzel-Gargand, Olivier; Kubart, Tomas; Edoff, Marika
Abstract : Herein, the performance of wide‐gap Cu(In, Ga)Se2 (CIGS) and (Ag, Cu)(In, Ga)Se2 (ACIGS) solar cells with In2 O3 :Sn (ITO) and In2 O3 :H (IOH) as transparent back contact (TBC) materials is evaluated. Since both TBCs restrict sodium in‐diffusion from the glass substrate, fine‐tuning of a NaF precursor layer is crucial. It is found that the optimum Na supply is lower for ACIGS than for CIGS samples. An excessive sodium amount deteriorates the solar cell performance, presumably by facilitating GaO x growth at the TBC/absorber interface. The efficiency ( η ) further depends on the absorber stoichiometry, with highest fill factors (and η ) reached for close‐stoichiometric compositions. An ACIGS solar cell with η = 12% at a bandgap of 1.44 eV is processed, using IOH as a TBC. The best CIGS device reaches η = 11.2% on ITO. Due to its very high infrared transparency, IOH is judged superior to ITO for implementation in a top cell of a tandem device. However, while ITO layers maintain their conductivity, IOH films show an increased sheet resistance after absorber deposition. Chemical investigations indicate that incorporation of Se during the initial stage of absorber processing may be responsible for the deteriorated conductivity of the IOH back contact in the final device. Abstract : Herein, the effect of silver alloying, absorber stoichiometry, and sodium supply on the performance of wide‐gap Cu(In, Ga)Se2 solar cells with transparent back contacts (TBCs) is studied. Tin‐ and hydrogen‐doped In2 O3 films are used as TBC materials. Efficiencies up to 12% (without antireflection coating) and very high infrared transparency are reached for an absorber bandgap of 1.44 eV.